Hidden risks associated with occupational pesticide exposure in women with breast cancer: High frequency of the Luminal B molecular subtype and occurrence of poor prognostic features - Isabella C. Cazagranda; Rafaela Frederico de Almeida; Lucca L. Smaniotto; Maria Paula de Andrade Berny; Carolina Coradi; Daniel Rech; Carolina Panis; Guilherme F. Silveira (PLoS ONE, 2026)
Human pesticide exposure is a common event in countries with strength conventional agriculture, such as Brazil. Despite evidence on the negative impact of pesticides on human health, the country stands out among the top three pesticide consumers globally. The implications of this scenario on rural workers health, particularly women, is completely neglected, resulting in chronic illness such as breast cancer. Objective: In this study, we analyzed the impact of occupational/household chronic exposure to pesticides on the clinicopathological profile of breast cancer in rural women from Paraná southwest, a predominantly rural landscape with large pesticide uses. Methods: A total of 349 women were included in the study. After a structured interview, women were categorized as exposed (n = 208) or unexposed (n = 141) to pesticides. Clinicopathological data were collected from medical records. Descriptive and inferential statistical methods were used to characterize and compare the sample. The Chi-square test and Fisher’s exact test were used to evaluate differences between the molecular subtypes and clinicopathological variables of patients. Results: Exposed patients had a prevalence of the Luminal B subtype (32.83%), while unexposed patients had a prevalence of the Luminal A molecular subtype (37.78%, p <= 0.05). Exposed patients also had higher disease recurrence (10.19%), chemoresistance (21.26%), than unexposed patients (p <= 0.05). Breast cancer patients exposed to pesticides were also more likely to have distant metastases (1.4 times) and lymph node invasion (1.3 times) compared to patients not exposed. Conclusions: These findings indicate that pesticide exposure favors the occurrence of more aggressive breast cancer.